Modeling and Simulation for the Drivetrain of Reversal Stubble-breaking Rototiller Based on SolidWorks and ADAMS - Li Chao Xu (Institute of Advanced Engineering and Science, 2014)
Rototiller was one kind of agriculture machinery which was widely used in the countryside, and traditional corotation stubble-breaking rototillers exsisted the deficiencies in narrow work width, high energy-consumption, poor vegetation coverage and soil-breaking performance. Aiming at the shortage of traditional rototillers, a reversal stubble-breaking rototiller was designed in this paper. On the basis of expounding the structure and working principle of the rototiller drivetrain, the virtual prototype model of the rototiller transmission was established by using SolidWorks, and its movement simulation was made by applying ADAMS, the simulation results in different engine speed of 65.685rad/s and 98.99rad/s showed that the rotating direction of each gear was in accordance with the real situation, the maximum rotational speed error between the simulation and theoretic calculation of the transmission was 1.02%, and the established virtual prototype had higher precision, which provided a prerequisite for dynamics analysis and optimization design of the drivetrain of reversal stubble-breaking rototiller. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4677